A Survey of Emergency Department Resources and Strategies Employed in the Treatment of Pediatric Gastroenteritis. (16th April 2013) - Kinlin, Laura M.; Bahm, Allison; Guttmann, Astrid; Freedman, Stephen B.; Baren, Jill M.
Abstract Objectives Although leading organizations have developed gastroenteritis management guidelines, little is known about emergency department (ED) use of clinical tools to improve outcomes. Our objective was to describe pediatric gastroenteritis clinical decision tools employed in EDs in the province of Ontario and to determine if a greater number of clinical decision tools are employed in academic, high‐volume institutions staffed primarily by emergency medicine (EM)‐trained physicians. Methods A cross‐sectional, Internet‐based survey was distributed in the summer of 2010 to medical directors and managers of Ontario EDs. Domains included patient population, general resources, and gastroenteritis‐specific strategies. Copies were requested of all gastroenteritis‐specific strategies to enable a content review. Results A total of 133 (83%) of 160 eligible participants responded. Practice guidelines, pathways, or order sets; medical directives; and printed discharge instructions were reported to be in use at 38 of the 133 (29%), 69 of 133 (52%), and 105 of 133 (79%) of the responding institutions, respectively. Oral rehydration therapy (ORT) is routinely initiated at triage in only 51 of the 133 of the EDs (38%). High‐volume institutions are more likely to have clinical practice guidelines, pathways, or order sets (p = 0.001) than low‐ and medium‐volume EDs. Physician training in EM was associated with the presence of medical directives for nursing administration of antiemetics and antipyretics (p = 0.04). Review of clinical practice guidelines, pathways, and order sets showed that only six of 27 gastroenteritis‐specific strategies reviewed were correctly classified, and 20 (74%) met prespecified quality criteria. Conclusions Clinical decision tools designed to improve pediatric gastroenteritis management are not commonly implemented. Such strategies are more common in high‐volume EDs and those staffed primarily by physicians with EM training.